A Cultural Capital Perspective of the Effect of a Government–Voluntary Sector Partnership for Enhancing Access to Postsecondary Education. (June 2014) - Lund-Chaix, A. A.; Gelles, Erna
Affordable access to postsecondary education is of growing concern for both families and policy makers. More students have chosen to continue their education after high school over the last several decades, though decisions whether and where to attend are often based on limited knowledge and financial resources. Increasing costs of attendance have sustained inequalities in access for students from varying economic, social, and racial groups—a problem that captures the attention of the government and voluntary sectors alike. The purpose of this article is to examine the effect of Oregon's government–voluntary sector partnership for improving access to postsecondary education: a private scholarship program and a volunteer mentoring program. In so doing, authors introduce cultural capital theory as a framework for studying nonprofit and voluntary sector activities. Authors suggest a need for further research on the utility of cultural capital in other policy areas that cut across sectors.